Systematic review of occupational exposure to cancer chemotherapy agents and adverse health outcomes - USA. National Institute of Environmental Health Sciences (Research Triangle Park, 2019)
"Many cancer chemotherapy agents have toxic properties that can lead to secondary cancers in patients receiving treatment for cancer, and are known to cause DNA damage and adverse pregnancy outcomes (e.g., fetal loss, congenital malformations). Occupational exposure to these agents was first documented in the 1970s and continues to occur, despite the issuance of safe handling guidelines in 1980s. While occupational exposure likely occurs at lower levels than those administered to patients or laboratory animals, the duration of exposure is longer and exposure may involve multiple chemotherapy agents."